Impact of N-acetylcysteine and Etodolac Treatment on Systolic and Diastolic Function in a Rat Model of Myocardial Steatosis Induced by High-Fat-Diet - Ender Topal, Askin; Akkoc, Hasan; Kelle, Ilker; Yilmaz, Sedat; Topal, Derya; Akkus, Murat (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2014)
Objectives: Obesity is a worldwide problem, leading to cardiomyopathy. Oxidative stress and inflammation have been reported to play significant roles in developing obesity cardiomyopathy. N-acetylcysteine is a glutathione prodrug that preserves liver against steatosis via constraining the production of reactive oxygen species. Etodolac is a nonsteroidal anti-inflammatory drug which has been demonstrated to protect liver against fibrosis. The aim of the present study was to evaluate and compare the effects of N-acetylcysteine and etodolac on impaired cardiac functions due to highfat- diet (HFD) induced myocardial steatosis in rats. Material and Methods: Thirty-two male Sprague-Dawley rats were randomly divided into four groups. Control group was maintained on standard-rat-basic-diet (SD) for 20 weeks, while HFD was given to three study groups for 20 weeks. Then N-acetylcysteine was given to one of the study groups (HFD+NAC), and etodolac to another group (HFD+ETD) as a supplement for 4 weeks while all groups were continued on SD. At the end of the study periods, hearts were examined by Langendorff technique and rat livers were evaluated histologically. Results: HFD and HFD+ETD groups presented with significantly higher steatosis and fibrosis in liver compared to other groups. HFD+NAC preserved diastolic functions. Also HFD+NAC and HFD+ETD groups had significantly better systolic funtions than HFD group. Conclusions: Obesity is associated with diastolic dysfunction rather than systolic dysfunction. NAC may protect the heart against diastolic dysfunction due to obesity. NAC and etodolac treatment improve systolic function, even in the absence of systolic dysfunction.
Keywords: etodolac